The Principal Physical Categories in the Early Greek and Indian Atomism - Šileikis, Saulius (Acta Orientalia Vilnensia, 2001)
The article deals with the Greek atomistic theory founded by Leucippus and Democritus and the Indian atomistic theory built by Kanada and Gotama. The analysis covers four principal physical categories which are common both to Greek and Indian atomists: substance, cause, non-being and movement. Greek and Indian atomists maintain that substance consists of eternal, indivisible and imperishable units or atoms. Greek atomists define the main feature of atoms as indivisibility, whereas Indian atomists define it as eternity. Greek and Indian atomists acknowledge mechanical causal relation. They also maintain that causal relation is universal, except for the movement of atoms (Greek atomists) and for the existence of atoms (Indian atomists). Greek atomists demonstrated the necessity to admit the concept of non-being in two ways: 1) “the non-real” (by means of principle of isonomia in order to overcome Parmenides’ monism) and also maintained, 2) “the unreal” or the void (using empirical arguments which were directed against Melissus). Indian atomists developed the concept of non-being as a result of the ontological differentiation between perceptible things and non-perceptible atoms. Since Greek atomists considered a perceptible thing to be a mere sum of atoms, they did not recognise the vanished thing to be a non-being one. The concept of the void was the essential argument for the explanation of movement in the Greek atomism. Yet Indian atomists regarded action (karman) as an implicit quality of substance and therefore did not recognize the void as the necessary condition of movement.